2020
DOI: 10.5539/ijef.v13n1p61
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Consequences of Idle Youth in Guatemala

Abstract: This paper analyzes the causes and consequences of the percentage of the youth population that is not working, in school or in traning, Neets, in Guatemala. The study rests on the estimation of regression equations that explain the percentage of Neet population in terms of variables associated with the labor market; other set of equations were estimated to assess the role that Neets have in the Guatemalan economy. The data employed was taken from the World Bank’s World Development Indicators. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The interest also stems from the impact of youth unemployment in terms of the loss of human capital and economic growth. Several authors have shown that youth unemployment is a preamble to self-employment, that is, to informality (Caceres, 2021a). of the variables are shown below in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest also stems from the impact of youth unemployment in terms of the loss of human capital and economic growth. Several authors have shown that youth unemployment is a preamble to self-employment, that is, to informality (Caceres, 2021a). of the variables are shown below in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Bluedorn et al (2021) have pointed out that there is no basis for forecasting which sectors will be the fastest to ijef.ccsenet.org International Journal of Economics and Finance Vol. 13, No.10;2021…”
mentioning
confidence: 99%